2019
DOI: 10.4054/demres.2019.40.14
|View full text |Cite
|
Sign up to set email alerts
|

‘Will the one who keeps the children keep the house?’ Residential mobility after divorce by parenthood status and custody arrangements in France

Abstract: BACKGROUND After divorce, at least one of the partners usually relocates and, according to past research, it is more often the woman. Women's housing conditions are likely to worsen. Divorces where children are involved are frequent and shared custody arrangements are becoming more common in Europe. OBJECTIVE This paper analyses the extent to which residential mobility after divorce is linked to parental status and child custody arrangements in France, a topic that remains largely unstudied. We assess not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 27 publications
(39 reference statements)
3
31
0
2
Order By: Relevance
“…However, not all mothers and their children can stay in the neighbourhood they lived in prior to separation: some of them leave at the time of separation, others leave some time thereafter. Previous studies have focused on the distance of moves among those who move following separation (e.g., Mulder and Malmberg 2011;Thomas, Mulder, and Cooke 2017b;Ferrari, Bonnet, and Solaz 2019), but the aspect of location continuity following separation has not been explicitly addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all mothers and their children can stay in the neighbourhood they lived in prior to separation: some of them leave at the time of separation, others leave some time thereafter. Previous studies have focused on the distance of moves among those who move following separation (e.g., Mulder and Malmberg 2011;Thomas, Mulder, and Cooke 2017b;Ferrari, Bonnet, and Solaz 2019), but the aspect of location continuity following separation has not been explicitly addressed.…”
Section: Resultsmentioning
confidence: 99%
“…A handful of studies have analysed the distance of a move after separation: these studies typically analyse the likelihood of moving followed by the distance moved among the movers using the Euclidian distance (in logged kilometres) between the origin and destination location. They show that when children are present, people tend to remain in their neighbourhood, as the social networks of the children are considered crucial (Gram-Hanssen and Bech-Danielssen 2008;Mulder and Malmberg 2011;Feijten andvan Ham 2007, 2013;Ferrari, Bonnet, and Solaz 2019). Most studies find that mothers stay in closer proximity to the pre-separation family home than fathers (Clark and Rivers 2012;Feijten and van Ham 2007), whereas Mulder and Malmberg (2011) find no difference.…”
Section: Location Continuity After Separationmentioning
confidence: 99%
“…Previous research found that women are more likely to leave the joint home at separation than men although this seems to reverse when children are present (Ferrari et al 2019;Fiori 2019;Mulder and Malmberg 2011;Mulder and Wagner 2010;Stone et al 2014). Additionally, women were found to be more likely to move from owner-occupied to rental dwellings than men in the Netherlands (Feijten 2005), a finding attributed to the generally lower socio-economic independence of women.…”
Section: Gender Differences In Separation and Elevated Residential Momentioning
confidence: 94%
“…They provide the first analyses of the residential and housing consequences of divorce for an Eastern European (Hungary by Murinkó 2019) as well as a Southern European country (Italy by Fiori 2019). The papers focus on the role of repartnering (Jalovaara and Kulu 2019;Schnor and Mikolai 2020), child custody arrangements (Ferrari, Bonnet, and Solaz 2019), the parental home (Murinkó 2019), location continuity (Schnor and Mikolai 2020), country context , and gender (all studies) for postseparation residential outcomes and trajectories .…”
Section: Discussion and Opportunities For Future Researchmentioning
confidence: 99%